Law Enforcement Towards Illegal Logging Perpetrators Based on Law Number 18 of 2013 Concerning Prevention and Eradication of Illegal Logging (P3H) - Muhammad Irvan Fachrozi (LEGAL BRIEF, 2022)
Illegal logging or illegal logging is logging, transporting or selling timber that is illegal or does not have a permit from local authorities. Deforestation, especially in the form of illegal logging, has caused state losses, damaged socio-cultural life and the environment, and increased global warming. Forest destruction has become a crime that has extraordinary, organized and transnational impacts carried out with a sophisticated modus operandi, has threatened the survival of people's lives so that in the context of preventing and eradicating effective forest destruction and providing a deterrent effect, a strong and capable legal basis is needed. ensure the effectiveness of law enforcement. The purpose of the article with the title "Law Enforcement Against Illegal Logging Perpetrators Based on Law Number 18 of 2013 concerning Prevention and Eradication of Illegal Logging (P3H" is to find out that the existence of this law can be used as an alternative to prevent acts of violating the law on forest crimes, especially illegal logging. and make it easier to deal with cases by referring to existing regulations in conducting research. The type of approach used is a normative legal approach.